So close, no matter how far: multiple paths connecting transcription to mRNA translation in eukaryotes. (16th August 2020) - Slobodin, Boris; Dikstein, Rivka
Abstract: Transcription of DNA into mRNA and translation of mRNA into proteins are two major processes underlying gene expression. Due to the distinct molecular mechanisms, timings, and locales of action, these processes are mainly considered to be independent. During the last two decades, however, multiple factors and elements were shown to coordinate transcription and translation, suggesting an intricate level of synchronization. This review discusses the molecular mechanisms that impact both processes in eukaryotic cells of different origins. The emerging global picture suggests evolutionarily conserved regulation and coordination between transcription and mRNA translation, indicating the importance of this phenomenon for the fine‐tuning of gene expression and the adjustment to constantly changing conditions. Abstract : This review discusses factors and elements that coordinate transcription and mRNA translation, suggesting an intricate level of synchronization underlying controlled and adaptable gene expression.